Endophytic colonisation of tobacco, corn, wheat and soybeans by the fungal entomopathogen Beauveria bassiana (Ascomycota, Hypocreales) - Russo, María Leticia (2015)
We demonstrate the effectiveness of three inoculation methods (foliar spray, seed immersion and root immersion) in establishing fungal the entomopathogen Beauveria bassiana as an endophyte in tobacco, corn, wheat and soybean. Colonisation of leaves by B. bassiana was assessed 7, 14, 21 and 28 days post-inoculation. There were significant differences (p < 0.001) in endophytic colonisation among the different inoculation techniques.